Epilepsi refrakter - Harsono, Harsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
In most patients with epilepsy the prognosis for seizure control is very good. However, about 10-20% of patients develop chronic or refractory epilepsy despite the advent of new antiepileptic drugs and intensive monitoring. Meanwhile, the definition of refractory or intractable epilepsy may vary, and a correct diagnostic work-up is of the utmost importance for the choice of treatment. Refractory epilepsy represents a challenge for both experimental and clinical research to obtain knowledge about why and how it develops and whether the condition can be prevented by early and adequate treatment. Definitions and epidemiology, experimental models, diagnostic evaluation, consequences, risk and costs, medical management, neurosurgery, and vagus stimulation are all important elements in managing refractory epilepsy. When dealing with therapy-resistant patients, a systemic step-by-step evaluation is essential. This includes: diagnosis, seizure/syndrome classification, aetiological considerations, review of drug treatment hitherto given, and evaluation of significant learning and psychosocial problems.Key words : refractory epilepsy - seizure - diagnostic evaluation - medical management - aetiological consideration